Association of changes in ER stress-mediated signaling pathway with lead-induced insulin resistance and apoptosis in rats and their prevention by A-type dimeric epigallocatechin-3-gallate. (December 2017) - Liu, Chan-Min; Ma, Jie-Qiong; Sun, Jian-Mei; Feng, Zhao-Jun; Cheng, Chao; Yang, Wei; Jiang, Hong
Abstract: A-type dimeric epigallocatechin-3-gallate (A-type-EGCG-dimer, AEd), a new proanthocyanidins dimer from persimmon fruits, has been shown to have health benefit effects. However, A-type-EGCG-dimer affects gluose metabolism in the liver and the underlying mechanism is not clarified. The present study aims to examine the protective effects of A-type-EGCG-dimer on Pb-induced hepatic insulin resistance, endoplasmic reticulum (ER) stress and apoptosis in rats. Male wistar rats exposed to 0.05% w/v Pb acetate in the drinking water with or without A-type-EGCG-dimer coadministration (200 mg/kg body weight/day, intragastrically) for three months. We found that A-type-EGCG-dimer and pioglitazone supplementation significantly deceased glucose and insulin levels in plasma as compared with the Pb group. A-type-EGCG-dimer markedly prevents Pb-induced oxidative stress, ER stress and apoptosis in livers. A-type-EGCG-dimer and pioglitazone reduced the expression levels of the GRP78, PEPCK, G6Pase, p-PERK, p-IRE1, p -JNK, ATF4, CHOP and increased p -AKT in livers of the Pb group. Moreover, A-type-EGCG-dimer reduced ROS production and restored the activities of SOD and GPx in livers. A-type-EGCG-dimer decreased Bax, cytosolic cytochrome c and cleaved caspase-3 and increased Bcl-2 in livers of Pb-exposed rats. Our results suggest that A-type-EGCG-dimer might be a potential natural candidate for the prevention of hepatic insulin resistance and apoptosis induced by Pb. Highlights: A-type EGCG dimer prevented Pb-induced hyperglycemia and hepatic insulin resistance in rats. A-type EGCG dimer inhibited the oxidative stress, ER stress and apoptosis in livers. A-type EGCG dimer reduced the expression levels of the PEPCK and G6Pase in livers. A-type EGCG dimer decreased the activities of p-PERK, p-IRE1, p -JNK and ATF4 in livers. A-type EGCG dimer inhibited the mitochondrial apoptotic pathway in livers of rats.